Derogations from the European Convention on Human Rights: The Case for Reform. (26th November 2020) - Wallace, Stuart
Abstract: This article examines State practice on derogations from human rights protection during states of emergency under Article 15 of the European Convention on Human Rights. The article presents statistical data on the use of derogations, offers analysis of the data and practice and advances a series of reform proposals. It is argued that Article 15 is being misused by States to derogate for protracted periods of time for entrenched emergencies and that emergency measures are remaining in place after declared emergencies have ended. Equally, States are not derogating in circumstances where they should for military operations, particularly extra-territorial military operations. It is argued that the European Court of Human Rights has been deferential in enforcing Article 15 and that reform is needed to address the problems identified. Reforms should include review procedures for emergency measures, enhanced procedures for notifying derogations and an amendment to facilitate extra-territorial derogations.